Analysis of the Reactivity Coefficient of the PWR Thorium Fuel - Rajagukguk, Santo Paulus; Purwadi, Purwadi; Bakhri, Syaiful (JURNAL TEKNOLOGI REAKTOR NUKLIR TRI DASA MEGA, 2024)
In design, control, and safety—especially in PWR reactors—the Reactivity Coefficient parameter is crucial. The validation of every new library for an accurate parameter prediction is then crucial. The purpose of this work is to determine the value of the reactivity coefficient at BOC and EOC using the WIMDS code based on ENDF/B-VIII.0 nuclear data files. The PWR-1175 MWe experiment critical reactors, which use Th-UO2 (thorium) fuel pellets, are a set of light water-moderated lattice experiments that are used for this purpose. The study is applied to the new cross-section libraries for WIMSD-5B and WIMSD-5B with ENDF/B-VIII.0 lattice code. The results showed that the fuel temperature reactivity coefficients for the PWR reactor at BOC and EOC using new libraries are – 4.07 pcm/K and – 2.72 pcm/K, respectively. Moderator Temperature Reactivity Coefficient at BOC and EOC are -1.8E-03 pcm/K and 3.73 pcm/K, respectively. Compared to the experimental data of the reactor core, the difference is in the range of 5.0 %. It can be concluded that for the PWR using thorium fuel as a model, all reactivity coefficients are negative and it is a good design for the safety of operation.